The impact of tourist companies website and specifications on the development of domestic tourism - an applied study on a sample of travel and tourism companies in the city of Baghdad - Shaimaa Abdulkreem Mousaand Prof.Muntaha Ahmed Mohammed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The issue of tourism companies has received a lot of interest from researchers in various fields in order to improve and develop their performance and measurement tools to suit different circumstances. The ability of tourism companies to continue facing their surroundings in which they operate does not depend only on plans and good preparation by the administration, and what is accompanied by continuous monitoring and follow-up of human resources and the methods of work followed and how to implement their plans and objectives required to achieve the desired results to increase the internal tourism movement, but it can be The location and specifications of the tourism companies are important as it is one of the factors that can contribute to the performance of the tourism companies. From the above, the main question can be raised (Can the location and specifications of the tourism companies affect the development of domestic tourism?) The two researchers reached a set of conclusions, the most important of which is that tourism companies have a strong relationship with the development of domestic tourism, and the location and specifications of tourism companies have an impact on the development of domestic tourism, and that domestic tourism preserves the local currency, achieves economic benefits for the country, and reduces leakage from the local economy. The research concluded with a set of appropriate recommendations that can benefit the relevant authorities in this field, including the necessity of developing domestic tourism through (coordination with the authorities concerned with infrastructure such as transport and with appropriate standards) and (enhancing the specifications of tourism companies using modern communication devices that enhance their activity) and (work Attracting cadres with tourism specializations to work in the field of tourism guidance to enhance the performance of tourism companies, which enhances their matches) and (promotion of social )media sites about their sites and all their work and trips